Investigation of the Influence of Nickel on the Behavior of Thermal Donors in Silicon - Ismaylov, Bayrambay K.; Zikrillayev, Nurulla F.; Ismailov, Kanatbay A.; Kamalov, Khayratdin U.; Saparov, Alloberdi K. (East European Journal of Physics, 2025)
This work presents a comprehensive theoretical and experimental study of the behavior of nickel impurity atoms in the silicon crystal lattice. The focus is on analyzing diffusion mechanisms, the energetic characteristics of interstitial nickel atoms, their interaction with defects and other impurities, as well as the formation of stable clusters within the crystal volume. First-principles quantum mechanical modeling was employed using the QuantumATK software, applying the Linear Combination of Atomic Orbitals (LCAO) method and the Local Density Approximation (LDA) exchange-correlation functional. Special attention was given to calculating the binding energy of nickel atoms in interstitial sites and estimating the activation energy for their migration along various crystallographic directions ([100] and [010]). The modeling results revealed that nickel atoms predominantly diffuse in interstitial positions with an activation energy around 0.31 eV, which aligns well with previously reported experimental data. It was found that interactions of nickel with oxygen, carbon impurities, and point defects have a minimal impact on diffusion processes. However, interactions with vacancies lead to the formation of stable nickel silicides and cause an increased concentration of nickel near the surface.The experimental part of the study confirmed the formation of nickel clusters under high-temperature treatments. Scanning Electron Microscopy (SEM), Secondary Ion Mass Spectrometry (SIMS), and Infrared (IR) microscopy revealed a high density and uniform distribution of clusters throughout the crystal volume. Cluster sizes ranged from 20 to 100 nm, with concentrations reaching approximately 1010 cm-3. These findings demonstrate that nickel acts as an effective gettering impurity, enhancing the electrophysical properties of silicon. The results provide valuable insights for optimizing the fabrication processes of high-efficiency silicon solar cells and microelectronic devices.